Extraction optimization of polysaccharides from Chinese rice wine from the Shaoxing region and evaluation of its immunity activities. (14th October 2014) - Shen, Chi; Mao, Jian; Chen, Yongquan; Meng, Xiangyong; Ji, Zhongwei
Abstract BACKGROUND Chinese rice wine is well known for its unique flavor and high nutritional value. It is of interest to investigate the functional components of Chinese rice wine and their health benefits. RESULTS Response surface design of three factors – pH, ethanol concentration and precipitation time – at three levels was utilized to optimize the extraction of Chinese rice wine polysaccharide (CRWP). The results indicated that the CRWP yield was 77.287% at the optimal levels for pH 8.4, ethanol concentration 88% and precipitation time 23 h. In addition, immune activity of CRWP was investigated by measuring body weight, spleen index and thymus index. Furthermore, immunity activity of CRWP was investigated by measuring lymphocyte proliferation, phagocytic index and phagocytic percentage of immunosuppressed mice. Compared with the control mice and model mice, it was found that CRWP has beneficial immune activities in vivo. CONCLUSION These findings indicate that CRWP has immune activities in vivo by modulating the immune response, and implies full development and utilization of the nutritional value of Chinese rice wine. However, further work will be conducted in the future to elucidate the structure–bioactivity relationship for CRWP. © 2014 Society of Chemical Industry